Desain Ilustrasi Tokoh Suryaputra Karna Mahabharata - Shiddiq H, Ryan Fatah Ash; Albar, Deni (Fakultas Desain Universitas Komputer Indonesia, 2021)
The positive values of life are embodied in culture and literary works that contain life values and also knowledge that has an influence on human life until now. Mahabharata is one of two ancient literary works originating from India, apart from Ramayana, as for several versions of this Mahabharata story. Mahabharata tells the story of the conflicts of the five Pandavas with Pandawa cousins namely 100 Kauravas, regarding the dispute over the rights of the Hasstinapura court government. Suryaputra Karna is one of the knights in the Mahabharata story and plays an important role in the storyline. The meaning of life that can be taken very much in the journey of life Karna, this design describes the meaning of heroism owned by Suryaputra Karna in the Mahabharata story. The conclusion obtained from this design, tells Karna's journey through many trials, slanders, and others that ultimately show the value of the character owned by Karna as an antagonist who can become a better figure and save or solve existing problems. The importance of the purpose of this design aims to preserve Karna characters and folklore that can be adapted into other media and can be easily accepted by teenagers today.